The sense of homeland on two popular Peruvian songs of the 20th century - Martínez Espinoza, Marino (2022)
This article introduces to the soundscape as an interdisciplinary tool directly linked to the use of different technology that reveals the interaction of humans with the acoustic environment. The article focuses on different technologies that expand the development and study of the soundscape, in addition to presenting some considerations, such as the location recording and the technology used, which not only configures the acoustic composition of the elements that integrate, but also their potential scientific application. The context of technological progress was taken into account, which has allowed obtaining better capture strategies, as well as contrasting examples, which allow us to expand our study in the cataloging and synthesis bird calls. Different problems that should be considered during the realization of the soundscape were discussed, such as background noise and imitative bird songs, which hinder the algorithmic recognition of the bird calls found in soundscapes. This creative discipline generates works that integrate technological tools that open up possibilities in both artistic and scientific work.